A Flexible and Transparent Zinc‐Nanofiber Network Electrode for Wearable Electrochromic, Rechargeable Zn‐Ion Battery. Issue 5 (30th November 2021) - Singh, Soram Bobby; Tran, Duy Thanh; Jeong, Kwang‐Un; Kim, Nam Hoon; Lee, Joong Hee
Abstract: The flexible electrochromic Zn‐ion battery (FE‐ZiB), a newly born energy‐storage technology having both electrochromic characteristics and energy‐storage capability in a single device, will be a promising technology for the future transparent wearable electronics. However, the current technology limits the fabrication of FE‐ZIB because the zinc (Zn) anode material is opaque and rigid. The development of a flexible and transparent Zn anode is the key factor to overcoming the current limitation. Here, for the first time, a flexible, transparent zinc‐nanofiber network anode electrode (Zn@Ni@AgNFs) is reported for an FE‐ZiB device that yields a remarkable electrochemical performance of a high areal capacity of 174.82 mA h m 2 at 0.013 mA cm −2 applied current density, high optical contrast (50%), and excellent mechanical flexibility. The fabricated FE‐ZiB device also exhibits a high volumetric energy density of 378.8 W h m −3 at a power density of 562.7 W m −3 . Besides, the FE‐ZiB demonstrates excellent electrochromic capability with a reversible color transition from a transparent in a discharged state (0.3 V) to a dark bluish‐violet in a charged state (1.6 V). These results highlight a new pathway for the development of transparent batteries for smart wearable electronic devices. Abstract : Electrodeposited Zn‐nanoflake@Ni@Ag nanofiber network as flexible and transparent anode and a porous honeycomb‐like PANi/HTE flexible electrode as the cathode; a wearable electrochromic, rechargeable Zn‐ion battery is fabricated. The fabricated wearable FE‐ZiB exhibits a high volumetric energy density of 378.8 W h m −3 at 562.7 W m −3 with the excellent reversible color transition from a transparent to a dark bluish‐violet.